Pengaruh Kepemimpinan terhadap Kinerja Guru dengan Budaya Organisasi sebagai Variabel Intervening pada SMP Negeri 12 Sungai Penuh - Lisa Atma Dewi; Sumarni Sumarni; Wahyu Juari Setiawan (Asosiasi Ilmuwan Pendidikan, Sosial, dan Humaniora Indonesia, 2025)
This study aims to analyze the influence of leadership on teacher performance with organizational culture as an intervening variable at SMP Negeri 12 Sungai Penuh. This research employs a quantitative approach with a causal study design. The population in this study consists of the school principal and all 30 teachers at SMP N 12 Sungai Penuh. The sample uses total sampling, where the author takes 100% of the existing population at SMP Negeri 12 Sungai Penuh, totaling 30 teachers. Data collection was conducted using questionnaires. Data analysis techniques utilized SEM PLS. The results show that teacher performance at SMP Negeri 12 Sungai Penuh is strong (125.33) with excellence in pedagogical and personality competencies. The principal's leadership is also strong (124.87) with communication as the best aspect, along with a strong organizational culture (124.83) in results orientation and stabilization. The research findings indicate that leadership has a positive and significant effect on teacher performance with a path coefficient of 0.423 (T-Statistics 5.096, P-Values 0.000). Leadership also significantly impacts organizational culture with a coefficient of 0.736 (T-Statistics 12.912, P-Values 0.000). Additionally, organizational culture positively influences teacher performance with a coefficient of 0.565 (T-Statistics 7.244, P-Values 0.000). Leadership also affects teacher performance through organizational culture as an intervening variable with an indirect path coefficient of 0.416 (T-Statistics 6.500, P-Values 0.000). This proves that organizational culture serves as a partial mediator in the relationship between leadership and teacher performance.